A new species of Coelogyne (Orchidaceae) from western Yunnan, China - Li, Rong; Dao, Zhi-Ling (Phytotaxa, 2014)
A new species of Orchidaceae, Coelogyne pianmaensis, is described and illustrated from western Yunnan, China. Morphologically, it is similar to Coelogyne corymbosa, but differs from the latter by having dark brown eyelike blotches surrounded by brownish-yellow on lip, 1-veined obovate-oblong leaves, 7-veined oblong-lanceolate sepals, shorter pedicel and ovary, and 7-veined petals.